Assessment of Microleakage of Class V Composite Resin Restoration Following Erbium-Doped Yttrium Aluminum Garnet (Er:YAG) Laser Conditioning and Acid Etching with Two Different Bonding Systems - Arbabzadeh Zavareh, Farahnaz (J Lasers Med Sci, 2013)
Introduction: The use of laser for cavity preparation or conditioning of dentin and enamelsurfaces as an alternative for dental tissue acid-etch have increased in recent years. Theaim of this in vitro study was to compare microleakage at enamel-composite and dentincompositeinterfaces following Erbium-Doped Yttrium Aluminum Garnet(Er:YAG) laserconditioning or acid-etching of enamel and dentin, hybridized with different bonding systems. Methods: Class V cavities were prepared on the lingual and buccal surfaces of 50 recentlyextracted intact human posterior teeth with occlusal margin in the enamel and gingival marginin the dentin. The cavities were randomly assigned to five groups: group1:conditioned withlaser (Energy=120mJ, Frequency=10Hz, Pulse duration=100μs for Enamel and Energy=80mJ,Frequency=10Hz, Pulse duration=100μs for Dentin) + Optibond FL, group2:conditioned withlaser + etching with 35% phosphoric acid + Optibond FL, group3:conditioned with laser+ Clearfil SE Bond, group 4 (control):acid etched with 35% phosphoric acid + OptibondFL, group 5 (control): Clearfil SE Bond. All cavities were restored using Point 4 compositeresin. All samples were stored in distilled water at 37°c for 24 h, then were thermocycled for500 cycles and immersed in 50% silver nitrate solution for 24 h. The teeth were sectionedbucco-lingually to evaluate the dye penetration. Kruskal-Wallis & Mann-Whitney testswere used for statistical analysis. Results: In occlusal margins, the least microleakage showed in groups 2, 4 and 5. Themaximum microleakage was observed in group 3 (P=0.009). In gingival margins, the leastmicroleakage was recorded in group2, while the most microleakage was found in group5 (P=0.001). Differences between 5 study groups were statistically significant (P<0.05).The microleakage scores were higher at the gingival margins. Conclusion: The use of the Er:YAG laser for conditioning with different dentin adhesivesystems influenced the marginal sealing of composite resin restorations.